Study Of Managers\' Communication Skills Based On The Staff\'s View In Shiraz University Of Medical Sciences - Ali Keshtkaran; Alireza Heidari; Peivand Bastani (Tehran University of Medical Sciences, 2012)
Background and Aim: Since managers' efficiency depends on their communication skills suitable for their employees, this study was conducted to determine such skills among Shiraz University of Medical Sciences (SUMS) managers. Materials and Methods: In this cross-sectional study, 298 SUMS employees working at different departments were selected through simple random sampling technique. The data-collection device was a 21-item questionnaire having 3 parts: verbal skill, effective listening, and feedback communication skills. The data were analyzed using SPSS software. Statistical tests employed included Pearson correlation, T-Test and ANOVA, and the level of significance was determined at 0.05. Results: The respondents' mean age was 32.7 years. Most of them were female, had a bachelor's degree, and worked in logistics department. According to their judgment, their managers had good verbal and effective listening skills, but were average in their feedback. The highest score for communication skills was reported for the students' department and the lowest score for the research department. Older and more experienced employees evaluated their manager's feedback skill (p= 0.001) at a lower level. The statistical test indicated a significant relationship between feedback and level of education (p= 0.001). Conclusion: It seems that the intermediate level of effective listening and feedback skills are due to the managers' lack of sufficient scientific and practical attention to the issue of communication. Therefore, it is recommended that educational workshops be held for managers to make them familiar with the importance of effective communication skills.